Self-Initiated Expatriates’ Success: The Influence of Adjustment and Perceived Organizational Support - Duan, Le (2020)
Abstract Self-initiated expatriates (SIEs) are different from traditional organization- backed expatriates, they work in foreign countries for different reasons (Lange & Meier, 2009; Andresen & Gustschin, 2012; Cao et al., 2014). Although the number of SIEs has been growing fast in the last few decades, SIEs have received much less attention from scholars and organizations (Crowley-Henry, 2007; Selmer & Cerdin, 2012). This study aims to investigate the relationship of perceived organizational support (POS) and cross cultural adjustment and the influence of these two factors on SIEs’ job satisfaction and turnover intention. Research hypotheses based on cross cultural adjustment (Black, Mendenhall and Oddou, 1991), organizational support theory (Eisenberger et al. 1986) and job satisfaction (Rue and Byaes, 2003). To analyze the relationship of these themes, this research adopted a quantitative research methodology, with a sample size of 129 questionnaire completed by SIEs in the UK. Data was analyzed SPSS 26. According to the results, the positive influence of POS on adjustment is confirmed. Meanwhile, this study finds that both POS and adjustment have a positive impact on SIEs’ job satisfaction. Besides, a new influence mechanism of POS and turnover intention is presented, in which job satisfaction plays a core mediator role.